Superconductivity from the condensation of topological defects in a quantum spin-Hall insulator - Yuhai Liu (Nature Portfolio, 2019)
Deconfined quantum critical points separate two phases with different broken symmetries, which puts them beyond the standard Landau theory of phase transitions. Here the authors present a model with a monopole-free deconfined quantum critical point, making it more amenable to detailed numerical studies.